Business correspondence in foreign language business course at technical university - Tatiana A. Fedorova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article deals with the problem of students’ communicative competence development based on foreign language business course. The paper focuses on active teaching models based on business correspondence, and contains the practical aspect.